Osteosarcoma arising from acetabulum extended to femoral head through round ligament: a case report. Issue 11 (24th November 2020) - Sasaki, Toru; Gokita, Tabu; Ae, Keisuke; Tanizawa, Taisuke; Hayakawa, Keiko; Funauchi, Yuki; Motoi, Noriko; Matsumoto, Seiichi
ABSTRACT: A skip metastasis was defined as a solitary separate focus of osteosarcoma occurring synchronously with a primary osteosarcoma in the absence of anatomic extension. The progression of skip metastasis is considered less likely because the articular cartilage acts as a barrier, so there have been few reports on progression of the extremity bone tumor across a joint. In our case report, the acetabular osteosarcoma progressed to the femoral head through the ligament of the femoral head. From the findings of magnetic resonance imaging and resected specimen and tissue specimen, we considered that the tumor progressed between ligament and synovial tissue covering the ligament, and not passing through the inside of the ligament. This case suggested a possibility that the tumor might progress through the synovium around the ligament of femoral head in the cases of osteosarcoma arising from the proximal femur and acetabulum.